Synthesis and crystal structure of two-slab scandates BaLa2–xDyxSc2O7 - Titov, Y.A.; Chumak, V.V.; Tymoshenko, M.V. (Reports of the National Academy of Sciences of Ukraine, 2022)
The conditions of isovalent substitution of La atoms for Dy atoms in A-positions of the BaLa2Sc2O7 two-slab perovskite-like structure of the BaLa2–xDyxSc2O7 type (0 ≤ x ≤ 1.0) have determined by X-ray powder diffraction methods. Tetragonal crystal structure (space group P42/mnm) of the BaLa2–xDyxSc2O7 phases with x equal to 0.2, 0.4, 0.5, 0.6, 0.8 and 1.0 was determined by the Rietveld method. Crystal structure of BaLa2–xDyxSc2O7 is based on the two-dimensional (infinite in the XY plane) perovskite-like blocks, consisting of two slabs of the deformed ScO6 octahedra connected by vertices. Adjacent blocks are shifted in relation to each other by half an edge of the perovskite cube and are alternated with one another in the direction of Z axis. The calculation of the valence bond sums of the Ba, La, and Dy atoms in the BaO9, BaO12, (La2–xDyx)O9 and (La2–xDyx)O12 poly- hedra showed an ordered distribution of the Ba and REE atoms in the slab perovskite-like structure of BaLa2–xDyxSc2O7. Ba atoms are localized only at 4f position inside the perovskite block, while REE atoms are placed only at 8j position at the boundary of the perovskite block. The adjacent perovskite-like blocks are sepa- rated by a slab of (La,Dy)О9 polyhedra and held together by —O—(La,Dy)— O— interblock bonds. It is estab- lished that the isovalent substitution of La atoms by Dy atoms leads to decrease the length of the (La,Dy)—O2 interblock distance, increase the degree of deformation of the interblocks (La,Dy)О9 polyhedra and to decrease the degree of the ScO6 octahedra deformation.